Parallel computing of multi-scale continental deformation in the Western United States: Preliminary results - Liu, Mian; Yang, Youqing; Li, Qingsong; Zhang, Huai (Physics of the earth and planetary interiors, 2007)
Lithospheric deformation in the western United States is one of the best examples of diffuse continental tectonics that deviate from the plate tectonics paradigm. Conceptually, diffuse continental deformation is known to result from (1) weak and heterogeneous rheology of continents and (2) driving forces that arise from plate boundaries as well as within the continental lithosphere. However, the dynamic interplay of continental rheology and driving forces, hence the geodynamics of continental tectonics, remains poorly understood. The heterogeneous rheology and multiple driving forces cause continents to deform over different spatiotemporal scales with different physical processes, yet most geodynamic models for continental tectonic avoid dealing with such multiphysics partly because of (1) the limited observational constraints of lithospheric structure and deformation, and (2) high demands on computing algorithms and resources. These constraints, however, have relaxed significantly in recent years to permit exploration of some of the multi-scale physics governing continental tectonics. Here we present preliminary results of modeling multi-scale tectonics in the western United States using parallel finite element computation. In a 3D subcontinental-scale model, we used fine numerical meshes to incorporate all major tectonic boundaries and rheological heterogeneities in the model to explore their interplay with tectonic driving forces in controlling active tectonics in the western US. In another model for the entire San Andreas Fault system, we explored strain localization and simulated fault behavior at multi-timescales ranging from rupture in seconds to secular fault creep in tens of thousands of years. These models can help to integrate data grids with distributed high-performance computing resources in the emerging geosciences cyberinfrastructure.